The role of HIF-1α in nicotine-induced root and bone resorption during orthodontic tooth movement. (12th October 2020) - Ullrich, Niklas; Schröder, Agnes; Bauer, Maria; Spanier, Gerrit; Jantsch, Jonathan; Deschner, James; Proff, Peter; Kirschneck, Christian
Summary: Background: In orthodontic tooth movement (OTM), pseudo-inflammatory processes occur that are similar to those of nicotine-induced periodontitis. Previous studies have shown that nicotine accelerates OTM, but induces periodontal bone loss and dental root resorption via synergistically increased osteoclastogenesis. This study aimed to investigate the role of hypoxia-inducible factor 1 alpha (HIF-1α) in nicotine-induced osteoclastogenesis during OTM. Materials/Methods: Male Fischer-344 rats were treated with l -Nicotine (1.89 mg/kg/day s.c., N = 10) or NaCl solution ( N = 10). After a week of premedication, a NiTi spring was inserted to mesialize the first upper left molar. The extent of dental root resorption, osteoclastogenesis, and HIF-1α protein expression was determined by (immuno)histology, as well as bone volume (BV/TV) and trabecular thickness (TbTh) using µCT. Receptor activator of nuclear factor of activated B-cells ligand (RANK-L), osteoprotegerin (OPG), and HIF-1α expression were examined at the protein level in periodontal ligament fibroblasts (PDLF) exposed to pressure, nicotine and/or hypoxia, as well as PDLF-induced osteoclastogenesis in co-culture experiments with osteoclast progenitor cells. Results: Nicotine favoured dental root resorptions and osteoclastogenesis during OTM, while BV/TV and TbTh were only influenced by force. This nicotine-induced increase does not appear to be mediated by HIF-1α, since HIF-1α was stabilized by force application and hypoxia, but not by nicotine. The in vitro data showed that the hypoxia-induced increase in RANK-L/OPG expression ratio and PDLF-mediated osteoclastogenesis was less pronounced than the nicotine-induced increase. Conclusions: Study results indicate that the nicotine-induced increase in osteoclastogenesis and periodontal bone resorption during OTM may not be mediated by hypoxic effects or HIF-1α stabilization in the context of nicotine-induced vasoconstriction, but rather by an alternative mechanism.